Designing a Fun English Vocabulary Card Application as a Means of Learning English Vocabulary for Elementary School Students - Setyawan, Haris; Arighi, Radityo Anindito; Isnanda, Reza Giga (Emerging Information Science and Technology, 2020)
English has been globally used for communication and studied by almost all countries. Therefore, understanding and being able to communicate in English is crucial. A lot of English learning is currently delivered using the lecture method, but there is no medium for learning English vocabulary in an application. This study aims to create a Fun English Vocabulary Card game to improve children’s English vocabulary. To design the learning model, the design of use case and activity diagrams was utilized. Based on the pre-test and post-test results, this game significantly increased children’s English vocabulary. The average pre-test score was 43.625, and the average post-test score was 95, which indicates that the educational game application could improve users’ knowledge and understanding of English vocabulary.